Covalent Organic Frameworks for Membrane Separation - Yuan‐Hang Jin; Meng‐Hao Li; Ying‐Wei Yang (Advanced Science)
Abstract Membranes with switchable wettability, solvent resistance, and toughness have emerged as promising materials for separation applications. However, challenges like limited mechanical strength, poor chemical stability, and structural defects during membrane fabrication hinder their widespread adoption. Covalent organic frameworks (COFs), crystalline materials constructed from organic molecules connected by covalent bonds, offer a promising solution due to their high porosity, stability, and customizable properties. The ordered structures and customizable functionality provide COFs with a lightweight framework, large surface area, and tunable pore sizes, which have attracted increasing attention for their applications in membrane separations. Recent research has extensively explored the preparation strategies of COF membranes and their applications in various separation processes. This review uniquely delves into the influence of various COF membrane fabrication techniques, including interfacial polymerization, layer‐by‐layer assembly, and in situ growth, on membrane thickness and performance. It comprehensively explores the design strategies and potential applications of these methods, with a particular focus on gas separation, oil/water separation, and organic solvent nanofiltration. Furthermore, future opportunities, challenges within this field, and potential directions for future development are proposed.